Studi Arsitektur Humanis dalam Relokasi Liponsos Sidoarjo - Aditya Saputra Firman Nurhaya; Intan Kusumaningayu; Mufidah Mufidah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
The relocation of the Social Welfare Shelter Environment (Lingkungan Pondok Sosial/Liponsos) in Sidoarjo represents a strategic effort to address social and spatial issues characterized by overcapacity, limited facilities, and an inadequate living environment that does not fully support the physical and psychological needs of people with social welfare problems (PMKS). These conditions indicate that the challenges faced by Liponsos are not merely social in nature but are also closely related to the quality of the built environment, which significantly influences the rehabilitation and recovery process of its residents. Therefore, a human-centered design approach is required in planning social service facilities. This study aims to analyze the application of humanistic architecture principles in the planned relocation of the Sidoarjo Liponsos as a foundation for creating a more livable, dignified, and user-oriented environment. The research employs a literature review method by collecting data from relevant books, journals, regulations, and previous studies. The analysis is conducted using descriptive and content analysis to examine the relationship between humanistic architectural principles and the needs of residents within social welfare facilities. The results indicate that the humanistic architectural approach is highly relevant to the relocation of Liponsos, particularly through spatial zoning based on levels of privacy and security, the provision of green open spaces and communal areas as media for social interaction and therapeutic activities, and the design of self-development spaces that support rehabilitation and empowerment. The implementation of these principles is expected to create a built environment that not only fulfills basic functional requirements but also supports psychological recovery, social stability, and sustainable improvement in the quality of life of PMKS residents.